The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1073/pnas.1413571111
|View full text |Cite
|
Sign up to set email alerts
|

Managing wildlife for ecological, socioeconomic, and evolutionary sustainability

Abstract: Selective harvesting of animals is widespread throughout the marine, freshwater, and terrestrial environments and affects a diverse list of species, including fish, mammals, birds, and reptiles (1). Such harvesting can cause changes in the distribution of phenotypic traits within target populations, often with undesirable biological and economic consequences. For example, selective harvesting has been linked to declines in the size of trophy horns in two antelope species in Zimbabwe (2) and of antlers in red d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…; Jørgensen et al. ; Andersen and Brander ; see also Bunnefeld and Keane ). Although exploited fish populations can consist of individuals of reduced average adult body size for both demographic and evolutionary reasons (Jørgensen et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Jørgensen et al. ; Andersen and Brander ; see also Bunnefeld and Keane ). Although exploited fish populations can consist of individuals of reduced average adult body size for both demographic and evolutionary reasons (Jørgensen et al.…”
Section: Introductionmentioning
confidence: 98%
“…Harvested populations have shown substantial alteration of morphological and life history traits with net documented changes in these types of traits averaging 18% and 25%, respectively (Darimont et al, 2009). Yet, distinguishing between ecological and evolutionary causes is neither a trivial nor a simple matter (Bunnefeld & Keane, 2014;Fenberg & Roy, 2008) and, in one recent study, demographic changes resulting from hunting explained observed phenotypic changes that were earlier attributed to evolution (Traill, Schindler, & Coulson, 2014). Still, potential evolutionary impacts of harvesting deserve consideration in applied management and conservation efforts, not least because they can be difficult to reverse (Bunnefeld & Keane, 2014;Coltman et al, 2003;Darimont et al, 2009;Fenberg & Roy, 2008).…”
mentioning
confidence: 99%
“…Yet, distinguishing between ecological and evolutionary causes is neither a trivial nor a simple matter (Bunnefeld & Keane, 2014;Fenberg & Roy, 2008) and, in one recent study, demographic changes resulting from hunting explained observed phenotypic changes that were earlier attributed to evolution (Traill, Schindler, & Coulson, 2014). Still, potential evolutionary impacts of harvesting deserve consideration in applied management and conservation efforts, not least because they can be difficult to reverse (Bunnefeld & Keane, 2014;Coltman et al, 2003;Darimont et al, 2009;Fenberg & Roy, 2008). 'Unnatural' selection from hunting can potentially also affect heritable behavioural traits (Allendorf & Hard, 2009), but there is still limited knowledge of the link between harvesting by humans and animal behaviour.…”
mentioning
confidence: 99%
“…Integral projection models offer a powerful tool for understanding the phenotypic and life‐history consequences of harvesting (Bunnefeld and Keane , Traill et al ). Our study offers valuable insights into how trophy hunting may influence reproductive value and mean antler size in red deer at unusually high hunting quotas (>50%).…”
Section: Management Implicationsmentioning
confidence: 99%